PERANCANGAN SISTEM FURNITUR MULTIFUNGSI UNTUK RUANG TREATMENT KLINIK KECANTIKAN DI SURABAYA - Viona Christi; The, Jaya Suteja; Wyna Herdiana (CALYPTRA, 2018)
Beauty clinics are very easy to find in urban areas. The use of shop / shop house as a clinic with limited space should be maximized as treatment room and doctor's office room. Inside the treatment room requires furniture.The purpose of this design is to design a furniture system for concise treatment rooms that can be used on a limited area. By using this furniture system, nurses and patients can move freely within the treatment room.Data collection methods used to design this furniture system is a qualitative method. Qualitative methods used are interviews and observation.From the design done, got the system furniture with a calm and relaxed color. The furniture system also uses Bauhaus design style, so the designed furniture system is not thematic and can be used at any beauty clinic.